Apparatus for the use of Zeolite as an Adsorbent in the Pressure Swing Adsorption (PSA) Technology for Oxygen Concentrator - Bahari, Yunus; Agustina, Sri; Kurniawan, Teguh (ASEAN Journal for Science and Engineering in Materials, 2023)
The equipment for using zeolite as an adsorbent in the Pressure Swing Adsorption (PSA) method for oxygen concentrator is presented in this research. Worldwide, oxygen is generally utilized for a variety of chemical reactions as well as medical applications. The need for medicinal oxygen has skyrocketed in all hospitals worldwide during the COVID-19 pandemic. To minimize the amount of processing power needed and make the most use of the adsorbent capacity, the PSA process must operate efficiently. Additional details about the zeolite's role as an adsorption medium to help PSA in the synthesis of oxygen may be found in this paper.